Sequential modulation of cardiac autonomic control induced by cardiopulmonary and arterial baroreflex mechanisms - Furlan, R.; Jacob, G.; Palazzolo, L.; Rimoldi, A.; Diedrich, A.; Harris, P. A.; Porta, A.; Malliani, A.; Mosqueda-Garcia, R.; Robertson, D. (Circulation (New York, N.Y.), 2001)
BACKGROUND: Nonhypotensive lower body negative pressure (LBNP) induces a reflex increase in forearm vascular resistance and muscle sympathetic neural discharge without affecting mean heart rate. We tested the hypothesis that a reflex change of the autonomic modulation of heartbeat might arise during low intensity LBNP without changes of mean heart rate. METHODS AND RESULTS: Ten healthy volunteers underwent plasma catecholamine evaluation and a continuous recording of ECG, finger blood pressure, respiratory activity, and central venous pressure (CVP) during increasing levels of LBNP up to -40 mm Hg. Spectrum and cross-spectrum analyses assessed the changes in the spontaneous variability of R-R interval, respiration, systolic arterial pressure (SAP), and CVP and in the gain (alpha(LF)) of arterial baroreflex control of heart rate. Baroreceptor sensitivity was also evaluated by the SAP/R-R spontaneous sequences technique. LBNP began decreasing significantly: CVP at -10, R-R interval at -20, SAP at -40, and the indexes alpha(LF) and baroreceptor sensitivity at -30 and -20 mm Hg, compared with baseline conditions. Plasma norepinephrine increased significantly at -20 mm Hg. The normalized low-frequency component of R-R variability (LF(R-R)) progressively increased and was significantly higher than in the control condition at -15 mm Hg. CONCLUSIONS: Nonhypotensive LBNP elicits a reflex increase of cardiac sympathetic modulation, as evaluated by LF(R-R), which precedes the changes in the hemodynamics and in the indexes of arterial baroreflex control.